Emotional intelligence among fourth and fifth grade students in the State of Kuwait: A comparative study between people with learning disabilities and normal people in light of some demographic variables - Althafeeri, Nawaf malaab; Alawadh, Abdulaziz Sadeq; Altamimi, Reem Yaqub (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the differences in emotional intelligence of 186 male and female students from fourth and fifth grades in the State of Kuwait in light of some demographic variables (pupil category, gender, and academic grade), After reviewing the theoretical literature, the researchers prepared a measure of emotional intelligence to reach the goals of the study, which had an appropriate degree of reliability and validity. The results of the study showed that there were statistically significant differences at the level of (0.01) between the mean scores of students with learning difficulties in favor of females. The study also showed that there are no statistically significant differences for emotional intelligence between ordinary students and those with learning difficulties, as well as the absence of statistically significant differences for the emotional intelligence of ordinary students between males and females, and finally, the study did not show the existence of statistically significant differences of emotional intelligence in relation to the grade variable, The study ended with a number of recommendations, as conducting training coerces for parents and teachers to help them providing the pupils with emotional intelligence skills. Incorporating the emotional intelligence skills in to the curriculum.
Keywords: Emotional intelligence; Learning disabilities and Primary school pupils